2021
DOI: 10.1177/19386400211055278
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Modified Broström for Chronic Lateral Ankle Instability With and Without Peroneal Tendon Exploration

Abstract: Background: It is not known how peroneal tendon exploration influences results after modified Broström for lateral ankle instability. We propose peroneal exploration at the time of modified Broström will have similar outcomes as no peroneal exploration. Methods: A retrospective analysis was performed of patients undergoing modified Broström with and without peroneal exploration. Foot and Ankle Outcome scores and data regarding military retention were gathered and compared. Results: Seventeen patients were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In addition, a previous report showed that no significant differences in return to duty and patient satisfaction were identified between patients undergoing modified Broström alone or modified Broström with peroneal exploration. 1 Finally, the follow-up duration was too short to evaluate the effect of recurrent instability on OA progression. It takes a long time, approximately 35 years, to develop OA since the initial injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous report showed that no significant differences in return to duty and patient satisfaction were identified between patients undergoing modified Broström alone or modified Broström with peroneal exploration. 1 Finally, the follow-up duration was too short to evaluate the effect of recurrent instability on OA progression. It takes a long time, approximately 35 years, to develop OA since the initial injury.…”
Section: Discussionmentioning
confidence: 99%